Commonwealth of Massachusetts : House of Representatives, Jan. 15, 1816. Ordered--that Messrs. Tudor, of Boston, Knapp, of Newburyport, and Trask, of Brimfield, be a committee, with such as the Honorable Senate may join, to make inquiries into the actual state of the following scientific and literary societies . - Quincy, Josiah, 1772-1864 ([publisher not identified], 1816)
Report on the financial standing of the American Academy of Arts and Sciences, the Massachusetts Historical Society, the Boston Atheneum, the Linnean Society and the Agricultural Society of Massachusetts compared to Peale's Museum, Dr. Hosack's botanical garden, the Medical Society of the State of New York, and the New York Historical Society, recommending that more funds be created in Massachusetts for support of such institutions. Preceded by the resolutions of the House and Senate appointing the members of the joint committee. Includes a proposed bill to incorporate the Massachusetts Institution as a measure to centralize the various societies' collections and libraries.